Mujeres que trabajan - Romero, Manuel; Ortiz, Mecha; Lusiardo, Tito; Marshall, Nini; Serrador, Pepita (Beverly Hills Video Home Producciones, 1980)
Retrata la situación de las mujeres trabajadoras en esos tiempos.